Peran Guru dalam Meningkatkan Minat Belajar Siswa Fatherless di Madrasah Ibtidiyah - Muhammad Rohan Saputra; Fathul Jannah; Nur Kholik Affandi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The phenomenon of fatherlessness, or the absence of a father figure in a child's life, may affect students’ emotional condition, motivation, and interest in learning. In this context, teachers play a crucial role in providing academic and emotional support within the school environment. This study aims to describe the role of teachers in enhancing the learning interest of fatherless students at MI Tijanul Jawahir. The research employed a qualitative approach with a phenomenological method. Data were collected through interviews, observations, and documentation involving four teachers and three fatherless students and were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that teachers serve as educators, mentors, facilitators, and evaluators in supporting students’ learning interest. Teachers implemented varied learning methods, provided individualized guidance, created a conducive learning environment, and conducted evaluations emphasizing students’ learning processes and efforts. The study found that teacher support increased students’ enjoyment, attention, interest, and engagement in learning while helping maintain stable learning interest despite the psychological challenges caused by father absence. Therefore, teachers play a significant role in supporting the academic and emotional development of fatherless students.